Quantifying losses in open-circuit voltage in solution-processable solar cells - Yao,J; Kirchartz,T; Vezie,MS; Faist,MA; Gong,W; He,Z; Wu,H; Troughton,J; Watson,T; Bryant,D; Nelson,J (Physical Review Applied, 2015)
The maximum open-circuit voltage of a solar cell can be evaluated in terms of its ability to emit light. We herein verify the reciprocity relation between the electroluminescence spectrum and subband-gap quantum efficiency spectrum for several photovoltaic technologies at different stages of commercial development, including inorganic, organic, and a type of methyl-ammonium lead- halide CH3NH3PbI3−xClx perovskite solar cells. Based on the detailed balance theory and reciprocity relations between light emission and light absorption, voltage losses at open circuit are quantified and assigned to specific mechanisms, namely, absorption edge broadening and nonradiative recombination. The voltage loss due to nonradiative recombination is low for inorganic solar cells (0.04–0.21 V), while for organic solar cell devices it is larger but surprisingly uniform, with values of 0.34–0.44 V for a range of material combinations. We show that, in CH3NH3PbI3−xClx perovskite solar cells that exhibit hysteresis, the loss to nonradiative recombination varies substantially with voltage scan conditions. We then show that for different solar cell technologies there is a roughly linear relation between the power conversion efficiency and the voltage loss due to nonradiative recombination.